Complex Involvement of the Extracellular Matrix, Immune Effect, and Lipid Metabolism in the Development of Idiopathic Pulmonary Fibrosis - Qian, Weiping; Xia, Shu; Yang, Xiaoyun; Yu, Jiaying; Guo, Bingpeng; Lin, Zhengfang; Wei, Rui; Mao, Mengmeng; Zhang, Ziyi; Zhao, Gui; Bai, Junye; Han, Qian; et al. (Frontiers in Molecular Biosciences, 2022)
Background and objective: Idiopathic pulmonary fibrosis (IPF) is an aggressive fibrotic pulmonary disease with spatially and temporally heterogeneous alveolar lesions and no early diagnosis biomarkers, thus this limits the understanding of IPF pathogenesis. Methods: Lung tissues from IPF patients with early-stage (n=7) from surgical lung biopsy and transplant-stage (n=2), and from the healthy controls group (n=6) were performed by mRNA sequencing, and verificated by qPCR, immunohistochemistry, western blot, and Single cell RNA sequencing(scRNA-Seq). Results: 380 transcripts (DETs) were differentially expressed in IPF, which were principally involved in extracellular matrix (ECM) remodeling, lipid metabolism, and immune effect. Of these DETs, 21 DETs (DMD, MMP7, POSTN, ECM2, MMP13, FASN, FADS1, SDR16C5, ACAT2, ACSL1, CYP1A1, UGT1A6, CXCL13, CXCL5, CXCL14, IL5RA, TNFRSF19, CSF3R, S100A9, S100A8, and S100A12) were selected and verified by qPCR. Differences in DMD, FASN and MMP7 were also confirmed at a protein level. scRNA-Seq was used to trace their cellular origin to determine which lung cells regulated them. The principal cell sources of DMD were ciliated cells, alveolar type I/II epithelial cells (AT cells), club cells, and alveolar macrophages (AMs); MMP7 derived from AT cells, club cells, and AMs while FASN originated from AT cells, ciliated cells and AMs. Conclusion: Overall, our data reveal a comprehensive transcriptional mRNA profile of IPF, and showed that ECM remodeling, lipid metabolism, and immune effect are complex during the early development of IPF, suggesting that no single cell, single gene, or pathway can account for the complex and heterogeneous nature of the disease.